The Profiles of Infantile Hemangiomas Patients - hidayati, Arie; earlia, Nanda; Sari, Ninda; Vella; Maulida, Mimi; asrizal, Cynthia wahyu (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Infantile hemangiomas (IH) are the most prevalent benign tumors in children, predominantly in girls. Most IH cases do not require treatment due to spontaneous involution, but 10% of cases do require early treatment due to size, location, and complications. Purpose: This study tried to define the profile, clinical aspects, and therapy of IH in Dr. Zainoel Abidin General Hospital, Banda Aceh. Methods: A descriptive approach using a retrospective analysis employing secondary data from the outpatient clinic's patient registration book. This study included all new cases of infantile hemangioma at the outpatient clinic general hospital between 2013 and 2021. Result: A total of 105 patients were involved in this study. The majority of IH patients (59%) were under the age of one year, with 64 female patients (61%) making the most visits to the pediatric clinic in 2017, 2018, and 2019 (77.1%). The most prevalent clinical features of skin lesions were nodules in 69 individuals (65.7%), and the most common site was the facial region (13.3%) in 44 patients. In 20 individuals, a combination of propanolol and oral corticosteroids was used as the most effective treatment strategy (19% ). Conclusion: Infantile hemangiomas is the most frequently reported benign tumor in children. Females are more likely than males to develop IH. The majority of IH is minor and normally resolves on its own without therapy. However, certain rare kinds of IH require clinician attention and systematic treatment.